2014
DOI: 10.1590/0102-778620130066
|View full text |Cite
|
Sign up to set email alerts
|

Importância das condições termodinâmicas nos eventos extremos de precipitação na cidade de Belém e região metropolitana

Abstract: RESUMOO objetivo desta pesquisa foi verificar a importância dos fatores termodinâmicos na ocorrência de eventos extremos de precipitação em Belém (PA) e região metropolitana, no período de agosto de 2008 a dezembro de 2009. O estudo da termodinâmica da atmosfera foi realizado a luz das teorias da Energia Potencial Disponível para a Convecção (CAPE) e, da Energia de Inibição da Convecção (CINE). Para classificar os eventos extremos de precipitação foi utilizado o método dos decis, a fim de associá-los aos valor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…In summary, the conditions of stability of the atmosphere, when analyzed case by case for DCE and SCE events -with precipitation ³ mm 15 mm h -1 , which occurred at different periods and times -show that when the influence of dynamic forces occurs, the value of CAPE can be elevated for both the occurrence of DCE and SCE, indicating that dynamic forcing plays an important role in the formation of intense convection, from the shallowest to the deepest (Mota and Nobre, 2006;Tavares and Mota, 2012 ;Gille and Mota, 2014;Santos, Mota and Rocha, 2014). And when doing an analysis, seasonal and for defined intervals, of average values -for events with precipitation ³ 1 mm h -1 -it was observed that there is a tendency for CAPE to be greater when DCE occurs, during the rainy season, and that SCEs need more convective energy available during the less rainy season.…”
Section: Atmosphere Stability Analysismentioning
confidence: 99%
“…In summary, the conditions of stability of the atmosphere, when analyzed case by case for DCE and SCE events -with precipitation ³ mm 15 mm h -1 , which occurred at different periods and times -show that when the influence of dynamic forces occurs, the value of CAPE can be elevated for both the occurrence of DCE and SCE, indicating that dynamic forcing plays an important role in the formation of intense convection, from the shallowest to the deepest (Mota and Nobre, 2006;Tavares and Mota, 2012 ;Gille and Mota, 2014;Santos, Mota and Rocha, 2014). And when doing an analysis, seasonal and for defined intervals, of average values -for events with precipitation ³ 1 mm h -1 -it was observed that there is a tendency for CAPE to be greater when DCE occurs, during the rainy season, and that SCEs need more convective energy available during the less rainy season.…”
Section: Atmosphere Stability Analysismentioning
confidence: 99%
“…Portanto, estes índices indicam as condições da estrutura termodinâmica vertical da atmosfera, permitindo uma análise ampla da formação da convecção úmida e consequente precipitação. Neste contexto, estudos têm sido feitos para avaliar o desempenho dos índices de instabilidade na previsibilidade de chuvas, principalmente de eventos extremos, na região tropical utilizando os dados de radiossondagens convencionais (Gille & Mota 2014;Oliveira & Oyama 2009;Tavares & Mota 2012). Como exemplo, se tem o trabalho de Santos, Mota & Rocha (2014), os quais utilizaram uma climatologia da Energia Potencial Disponível para a Convecção (CAPE), para verificar a possibilidade da ocorrência de convecção e associando esse índice a eventos extremos de precipitação em Belém-PA. Os resultados mostraram, que a CAPE não é condição suficiente para a formação de nuvens e, consequentemente, de precipitação, pois há outras forçantes de meso e grande escala que contribuem decisivamente para a modulação do clima da cidade.…”
Section: Introductionunclassified